The Effects of LIT and MLR-Bf on Immune Biomarkers and Pregnancy Outcomes in Women With Previous Early Recurrent Miscarriage: A Retrospective Study - Meng, Lili; Tan, Jianping; Du, Tao; Lin, Xianghua; Zhang, Shuning; Nie, Xiaolu; Xie, Haitian; Lin, Jizong; Zhang, Jianping; Hui, Chen (Frontiers in Immunology, 2021)
Background: Immunological failure during pregnancy is considered as one of the etiologies of recurrent miscarriage (RM). The decreased production of mixed lymphocyte reaction blocking factors (MLR-Bf) may play a major role in this condition. Lymphocyte immunotherapy (LIT) which induces the production of MLR-Bf has been used in treating RM patients since 1984. However, the effectiveness of LIT is currently being heatedly debated. In addition to that, possible changes to the maternal immune system upon induced MLR-Bf production by LIT remains unclear. Objectives: To explore the possible impacts that MLR-Bf may have on the expression of immune biomarkers and pregnancy outcomes, and deduce whether the prevention of miscarriages is possible with LIT or MLR-Bf in RM patients. Material and methods: Women with previous early RM (eRM) were enrolled in this retrospective study after they got pregnant again. LIT was implemented before pregnancy and during the first trimester. MLR-Bf and immune biomarkers were checked as the clinical routine. Patients were followed up until more than 12 gestational weeks. Levels of immune biomarkers and successful pregnancy rates were compared between MLR-Bf- group and MLR-Bf+ group stratified by LIT. Independent associations between LIT, or MLR-Bf, and miscarriage were estimated. All data management and analysis were conducted using SPSS 20.0. Results: A total of 1038 patients, 497 MLR-Bf- (49 women after LIT), and 541 MLR-Bf+(463 women after LIT) were included in the study. Percentage of Lymphocytes, the ratio of CD4+ T cells/Lymphocytes, and levels of some rheumatoid biomarkers (Anti-U1-nRNP, Anti-SAA-52kd, and Anti-CENOP B) were statistically higher in the MLR-Bf+ group than in the MLR-Bf- group among women without LIT. The successful pregnancy rate was statistically higher in the MLR-Bf+ group than the MLR-Bf- group (66.7% vs 51.0%, P=0.028) among women with LIT. Meanwhile, LIT was estimated to have an independent negative association with miscarriage. Conclusion: Levels of immune biomarkers were different in women with and without MLR-Bf when stratified by whether received LIT. Not MLR-Bf, but LIT has an independent protective effect on miscarriage.